Transparência e opacidade na seleção de estratégias de relativização no português - Camacho, Roberto Gomes [UNESP] (My University, 2012)
This paper aims at examining the hypothesis that the choice among the different strategies of relativization available in the Portuguese grammar is motivated by a lesser or greater degree of transparency between form and meaning, which implies, correlatively, lesser or greater degree of ease in cognitive processing. In addition, the lesser or greater degree of transparency allows to postulate a hierarchical ordering for the strategies in correspondence to a greater or a lesser degree of ease in cognitive processing.

O objetivo deste trabalho é examinar a hipótese de que a seleção entre as diferentes estratégias de relativização disponíveis na gramática do português é motivada por um grau maior ou menor de transparência entre forma e conteúdo, o que implica, correlativamente, grau maior ou menor de facilidade no processamento cognitivo. Além disso, o grau maior ou menor de transparência permite postular uma ordenação das estratégias correspondente a uma escala hierárquica em termos de maior ou menor grau de facilidade de processamento cognitivo.
Transparency and opacity in the choice of relativization strategies in portuguese
Keywords: estratégias de relativização; transparência; iconicidade; economia; relativization strategies|transparency; opacity; iconicity; economy